The High Price of Mahar Mayam in Aceh Tradition: Analysis of Mahar Levels from the Perspective of the Qur'an - Muhammad Fadhil (AN NUR: Jurnal Studi Islam, 2025)
This study discusses the dowry in the perspective of the Qur'an and its relevance to the tradition of mahar mayam in Aceh. The phenomenon of declining marriage rates in Aceh, one of the causes of which is the high price of gold dowries (mayam), forms the background to this study. The purpose of this study is to analyze the compatibility between the practice of dowries in Acehnese tradition and the principles of the Qur'an. The method used is qualitative with a library research approach. The primary data sources included the Qur'an, the book Jeunamee: Konsep dan Makna Mahar dalam Masyarakat Aceh (Jeunamee: The Concept and Meaning of Dowry in Acehnese Society) by Essi Hermaliza Soraya Devy, and Bid?yah f? al-Tafs?r al-Maw???? by al-Farmawi, which were used as theories. Secondary data were obtained from tafsir books and relevant literature related to dowry and Acehnese culture. The results of the study show that the Qur'an does not specify the amount of dowry, so giving a large dowry is permissible as long as it does not burden the prospective husband. In Acehnese tradition, 3.3 grams of gold is called one mayam, and the amount of dowry generally ranges from 10 to 30 mayam, depending on the social background and education of the prospective bride and groom. The dowry tradition in Aceh is in line with the principles of the Qur'an, but the Qur'an emphasizes the ease of marriage so that the dowry does not become an obstacle for the couple.